If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 1) = (2x + 1) + (2x + 1) + (2x + 1) Reorder the terms: 3(1 + 2x) = (2x + 1) + (2x + 1) + (2x + 1) (1 * 3 + 2x * 3) = (2x + 1) + (2x + 1) + (2x + 1) (3 + 6x) = (2x + 1) + (2x + 1) + (2x + 1) Reorder the terms: 3 + 6x = (1 + 2x) + (2x + 1) + (2x + 1) Remove parenthesis around (1 + 2x) 3 + 6x = 1 + 2x + (2x + 1) + (2x + 1) Reorder the terms: 3 + 6x = 1 + 2x + (1 + 2x) + (2x + 1) Remove parenthesis around (1 + 2x) 3 + 6x = 1 + 2x + 1 + 2x + (2x + 1) Reorder the terms: 3 + 6x = 1 + 2x + 1 + 2x + (1 + 2x) Remove parenthesis around (1 + 2x) 3 + 6x = 1 + 2x + 1 + 2x + 1 + 2x Reorder the terms: 3 + 6x = 1 + 1 + 1 + 2x + 2x + 2x Combine like terms: 1 + 1 = 2 3 + 6x = 2 + 1 + 2x + 2x + 2x Combine like terms: 2 + 1 = 3 3 + 6x = 3 + 2x + 2x + 2x Combine like terms: 2x + 2x = 4x 3 + 6x = 3 + 4x + 2x Combine like terms: 4x + 2x = 6x 3 + 6x = 3 + 6x Add '-3' to each side of the equation. 3 + -3 + 6x = 3 + -3 + 6x Combine like terms: 3 + -3 = 0 0 + 6x = 3 + -3 + 6x 6x = 3 + -3 + 6x Combine like terms: 3 + -3 = 0 6x = 0 + 6x 6x = 6x Add '-6x' to each side of the equation. 6x + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3x-11+1/x-8 | | 11=y+13 | | 0.9(9x+6)=2.5-(x-3) | | -3n-1/2(-4-4n)=7 | | 283=3.14(5)l+(3.14)25 | | 5+(-3w+-12)=w+-7 | | -12.2y-8.68=-11.34-13.6y | | 2e^6= | | 3(3x-2)=7(x+6)+7 | | 1/2x-5=3x-10 | | 9x+6y=150 | | 283=3.14(5)l+25 | | 2(5x-3)-1=13 | | 6v+6=4v+2(v+3) | | 3.1-0.2a=1.5 | | m+m+5+m+8=84 | | 5-2p=7 | | -7.26+18p=6p-2.22+12.3p | | 3x+4y=75 | | 4x-48=36 | | 25.50x=12.50 | | -1=c-6 | | 6x+(3x-2)=14 | | -7v-5=-5v-9 | | x^2-7/3x-2/3 | | X+-5=6 | | -20+2x=30 | | 184=6y+4 | | -2n(9-10n)= | | 25.50=13.50 | | 8/3=32/x | | 6.2h+51.4h=4.8h+5 |